Impact of Climate Change on Mali’s Agro-Pastoralists and their Adaptation Strategies - Tapily, Assa; Olufayo, A. A.; Rüdiger, Anlauf; Diarra, Mamadou (Research Advances in Environment, Geography and Earth Science Vol. 5, 2024)
Many people in African countries derive their livelihoods from agriculture and livestock. Climate Change is a serious problem for the whole world, it is explained by an upward trend in temperatures measured during the last decades of the 20th century and also a decrease in increased variability of precipitation. Therefore, unfavourable environmental and climatic conditions render them more vulnerable to increasing food insecurity and poverty rates. However, few studies have investigated how farmers’ adaptation strategies affect farm productivity and household food security in the Sahelian region, notably Mali. This study aims to examine the impacts of climate change on agro-pastoralists and to analyse the adaptation strategies in Mali. Quantitative and qualitative surveys were carried out among the target groups as well as other actors in the field of climate change. For this purpose, an analysis of daily rainfall and temperature data from 1960 to 2020 over Bamako, Ségou and Sikasso stations was carried out. Field surveys were conducted among 355 agropastoralists in three regions of Mali to assess the impacts and adaptation strategies of agropastoralists. The analysis of climate data showed a downward trend in overall rainfall. As for the temperature, it shows an upward trend over the series from 1960 to 2020 at the stations of Ségou, Sikasso and Bamako. The results of the surveys revealed that 61% of agro-pastoralists were victims of at least one climate-related disaster and which caused several damages. Agropatoralists use adaptation strategies such as organic fertilizers, changing planting dates and growing short-duration maize varieties to mitigate against the negative effects of climate change. The use of organic fertilizers and short-duration use of improved varieties promotes agricultural productivity and food security. We conclude that building agro-pastoralists adaptive capacity tends to reduce their vulnerability to climate change by increasing crop yields and food security. Promotion of sustainable farming practices should be adopted such as conservation agriculture, agroforestry, and water management techniques, to enhance resilience and reduce the ecological footprint of agriculture.